Mindfulness and Its Impact on Resilience, Sports Performance and Well Being of Athletes: A Literature Review (Trinity Journal of Management, IT & Media (TJMITM), 2022)
This paper aims to synthesize the available literature focusing on mindfulness-based- interventions and their effect on sports performance and sports performance-related variables, namely, flow. The performance of an athlete also depends on his mental and physical health therefore, this review also focused on the association between mindfulness and the well-being of athletes.Design/Methodology/ApproachA structured literature search was conducted by researchers to identify and select relevant studies using electronic databases, namely, Web of Science and PubMed. Once decided, the keyword categories were combined with the Boolean operators ‘AND’/‘OR’ to search for articles in different databases, and research papers that were overlapping after searching different databases have been removed to avoid any kind of duplication.FindingsThis study explores Mindfulness and Sports performance literature, which will provide valuable insights to sports psychologists, athletes, and coaches. This review shows that most of the studies have concluded that athletes have benefitted by adopting mindfulness training in terms of enhanced performance, increased flow, improvements in attention, and enhanced well-being. Although this review gives some evidence regarding the effectiveness and efficacy of mindfulness-based interventions in enhancing sports performance, flow, and well- being, it is still recommended that more extensive and high-quality research studies are required in diverse sports settings.OriginalityThis review not only focuses on sports performance as an outcome of mindfulness training interventions but also throws light on sports performance-related variables. Another important aspect of this review paper is that it also focuses on the well-being of athletes.
Keywords: Mindfulness; Sports Performance; Flow; Well-being; Resilience; Mental Health; Review